CEACAM1 Is Associated With the Suppression of Natural Killer Cell Function in Patients With Chronic Hepatitis C. Issue 10 (25th September 2018) - Suda, Takahiro; Tatsumi, Tomohide; Nishio, Akira; Kegasawa, Tadashi; Yoshioka, Teppei; Yamada, Ryoko; Furuta, Kunimaro; Kodama, Takahiro; Shigekawa, Minoru; Hikita, Hayato; Sakamori, Ryotaro; Fukuhara, Takasuke; et al.
Abstract : Natural killer cells (NK cells) play an essential role in the immunological mechanism underlying chronic hepatitis C (CHC). Impairment of NK cell function facilitates persistent infection with hepatitis C virus (HCV) and hepatocellular carcinogenesis. However, the mechanism by which NK cell activity is suppressed in CHC is not completely understood. In this study, we focused on carcinoembryonic antigen–related cell‐adhesion molecule 1 (CEACAM1). CEACAM1 is thought to suppress NK cell function. We examined the effect of CEACAM1 on NK cell function in CHC. We investigated the function of CEACAM1 in vitro using Huh7.5.1 cells and the HCV‐Japanese fulminant hepatitis (JFH)‐1 strain. We analyzed serum CEACAM1 level, NK cell function, and CEACAM1 messenger RNA (mRNA) level in human liver samples. Levels of CEACAM1 on the cell surface, CEACAM1 mRNA levels, and soluble CEACAM1 levels in supernatants were significantly higher in Huh7.5.1 cells infected with JFH‐1 (Huh7.5.1/JFH‐1 cells) than in Huh7.5.1 cells. Significantly higher NK cell cytotoxicity was observed toward K562 cells after coculture with CEACAM1 knockout Huh7.5.1/JFH‐1 cells than after coculture with Huh7.5.1/JFH‐1 cells. CEACAM1 expression was induced by the HCV E2 glycoprotein in HCV infection. Significantly higher serum CEACAM1 levels were detected in patients with CHC compared with healthy subjects and patients who achieved sustained virological responses. The expression of CD107a on NK cells from patients with CHC was negatively correlated with serum CEACAM1 levels. Significantly higher levels of CEACAM1 mRNA were detected in HCV‐infected livers compared with uninfected livers. Conclusion: CEACAM1 expression was induced in hepatocytes following HCV infection and decreased NK cell cytotoxicity. These results demonstrate a possible role for CEACAM1 in the pathogenesis of CHC and hepatocellular carcinoma progression. Abstract : CEACAM1 expression on hepatocytes is induced by HCV E2 glycoprotein. Increased CEACAM1 expression reduces NK cell cytotoxicity by cell‐cell contact. HCV E2 glycoprotein‐induced CEACAM1 may be associated with persistent infection and the development of HCC